2017
DOI: 10.1097/qad.0000000000001558
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral initiation is associated with increased skeletal muscle area and fat content

Abstract: Objective A greater burden of physical function impairment occurs in HIV-infected adults; the impact of antiretroviral therapy (ART) initiation on muscle density (less dense = more fat), a measure of muscle quality, is unknown. Design AIDS Clinical Trials Group Study A5260s, a cardiometabolic substudy of A5257, randomized HIV-infected, ART-naïve adults to ritonavir-boosted atazanavir, darunavir, or raltegravir with tenofovir/emtricitabine backbone. Single-slice abdominal computed tomography (CT) scans from b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…In the Multicenter AIDS Cohort Study, men with HIV (~57 years old) on antiretroviral therapy had lower thigh muscle density (by 1 HU), compared to their HIV-uninfected peers (~54 years old), and lower thigh muscle density was correlated with greater VAT area and weaker grip strength [7]. We have previously shown that antiretroviral therapy initiation was associated with a decrease in trunk muscle density (−0.87 to −2.4 HU across muscle groups) over 96 weeks [40]. Lastly, in a three month intervention of metformin with or without aerobic + resistance exercise among lipodystrophic men and women with HIV (n=25), participants in the exercise + metformin arm experienced greater increase in thigh muscle attenuation (median change 2.0; IQR 0.5, 5.0 HU) compared to metformin only arm (−1.0, IQR −3.5, 0; p=0.04) [41].…”
Section: Discussionmentioning
confidence: 99%
“…In the Multicenter AIDS Cohort Study, men with HIV (~57 years old) on antiretroviral therapy had lower thigh muscle density (by 1 HU), compared to their HIV-uninfected peers (~54 years old), and lower thigh muscle density was correlated with greater VAT area and weaker grip strength [7]. We have previously shown that antiretroviral therapy initiation was associated with a decrease in trunk muscle density (−0.87 to −2.4 HU across muscle groups) over 96 weeks [40]. Lastly, in a three month intervention of metformin with or without aerobic + resistance exercise among lipodystrophic men and women with HIV (n=25), participants in the exercise + metformin arm experienced greater increase in thigh muscle attenuation (median change 2.0; IQR 0.5, 5.0 HU) compared to metformin only arm (−1.0, IQR −3.5, 0; p=0.04) [41].…”
Section: Discussionmentioning
confidence: 99%
“…However, given the recent animal model of enhanced cholesterol excretion in the gut following statin therapy exposure [4], it is likely that future additional studies in the interaction between statin and gut dysbiosis in the HIV-infected population will ensue. Because HIV infection is also associated with increased frailty[49], and particularly decrease in lean body mass [50, 51] and physical strength [52], statin therapy has been evaluated address these problems. For instance, in a study of 147 HIV-infected adults on ART followed for 96 weeks, rosuvastatin 10mg was associated with a non-statistically significant increase in lean body mass [53], indicating a potential role of statin therapy in decreasing muscle frailty and its associated complications in this population.…”
Section: Statin Therapy and End-organ Dysfunctionmentioning
confidence: 99%
“…1, Mayer et al (1989); 2, Goodpaster, Kelley, et al (2000); 3, Hicks et al (2005a); 4, Hicks et al (2005b); 5, Komiya et al (2006); 6, Laroche and Cintas (2010); 7, Anderson et al (2013); 8, Anderson et al (2014); 9, Antoun et al (2013); 10, Miljkovic et al (2013); 11, Therkelsen et al (2013); 12, Therkelsen et al (2016); 13, Kim et al (2014); 14, Akahori et al (2015); 15, Aust et al (2015); 16, Malietzis et al (2015); 17, Malietzis, Currie, et al (2016); 18, Malietzis, Johns, et al (2016); 19, Malietzis, Lee, et al (2016); 20, Cushen et al (2016); 21, Hayashi et al (2016); 22, Kumar et al (2016); 23, Looijaard et al (2016); 24, Montano‐Loza et al (2016); 25, Rollins et al (2016); 26, Wang et al (2016); 27, Atlan et al (2017); 28, Azuma et al (2017); 29, Bye et al (2017); 30, Erlandson et al (2017); 31, Locke et al (2017); 32, Loumaye et al (2017); 33, Okumura et al (2017b); 34, Rier et al (2017); 35, Rier et al (2018); 36, Shachar, Deal, Weinberg, Williams, et al (2017); 37, Shachar, Deal, Weinberg, Nyrop, et al (2017); 38, van Roekel et al (2017); 39, Williams et al (2017); 40, Williams et al (2018); 41, Choi et al (2018); 42, Rodrigues and Chaves, (2018); 43, Silva de Paula et al (2018); 44, Souza et al (2018); 45, Versteeg et al (2018); 46, Charette et al (2019); 47, Kiss et al (2019); 48, Zhang et al (2018); 49, Coats et al (2018); 50, Vella et al (2018); 51, Dohzono et al (2019); 52, van Baar et al (2018); 53, ...…”
Section: Resultsmentioning
confidence: 99%
“… 1, Mayer et al (1989); 2, Goodpaster, Kelley, et al (2000); 3, Ricq and Laroche, (2000); 4, Hicks et al (2005a); 5, Hicks et al (2005b); 6, Komiya et al (2006); 7, Anderson et al (2013); 8, Anderson et al (2014); 9, Antoun et al (2013); 10, Martin et al (2013); 11, Miljkovic et al (2013); 12, Akahori et al (2015); 13, Aust et al (2015); 14, Fujiwara et al (2015); 15, Malietzis et al (2015); 16, Malietzis, Currie, et al (2016); 17, Malietzis, Johns, et al (2016); 18, Malietzis, Lee, et al (2016); 19, Boer et al (2016); 20, Cushen et al (2016); 21, Hayashi et al (2016); 22, Kumar et al (2016); 23, Looijaard et al (2016); 24, Montano‐Loza et al (2016); 25, Pędziwiatr et al (2016); 26, Rollins et al (2016); 27, Sjøblom et al (2016); 28, Tamandl et al (2016); 29, Wang et al (2016); 30, Atlan et al (2017); 31, Bye et al (2017); 32, Chu et al (2017); 33, Daly et al (2017); 34, Daly, Ní Bhuachalla, et al (2018); 35, Erlandson et al (2017); 36, Kubo et al (2017); 37, Locke et al (2017); 38, Loumaye et al (2017); 39, Okumura et al (2017a); 40, Okumura et al (2017b); 41, Rier et al (2017); 42, Rier et al (2018); 43, van Grinsven et al (2017); 44, Van Rijssen et al (2017); 45, van Roekel et al (2017); 46, Choi et al (2018); 47, Matsumoto et al (2018). 48, Ní Bhuachalla et al (2018); 49, Souza et al (2018); 50, Versteeg et al (2018); 51, Graffy et al (2019); 52, Charette et al (2019); 53, Kiss e...…”
Section: Resultsmentioning
confidence: 99%